Stylize Airbrush / Siti Aminah Jaafar ... [et al.] - Jaafar, Siti Aminah; Mansur, Mastura; Husni, Hilmi Amir Hamzah; Yusof, Abdullah; Ahmad Sha'er, Imran (Faculty of Art and Design, 2004)
Stylize Airbrush is the name of our partnership after all partners agreed with it. We serve customer with a new design of airbrushing as well as providing them with the most quality airbrush design. We are a shop that specializes in designing and airbrushing only and also high quality with the new technology to attract our customer. There is no other shop that can do better than Stylize Airbrush . Stylize Airbrush is the only answer to the airbrushing lover also for person who like funky and brave . We receive customer needs from teenagers to big company . For example the company needs to paint their livery to put the corporate image to the vehicle . That is the way that we can do, we can make some different. We are situated at Seksyen 9 , Shah Alam . The main purpose we are using that area because it is in the middle of the Shah Alam city. We actually new and we need to know how the people will react with our new services and technology. We will be ready for the risk of the people that would not accept our new style in painting. We confident that we can brake the market even though many competitors around .